Regra de Sinais de Descartes para polinômios ortogonais - Siqueira, Gustavo de Toledo [UNESP] (2015)
The main objective of this text is the study of the Descartes' rule of signs and the generalized Descartes' rule of signs. We also present an application of the generalized Descartes' rule of signs to orthogonal polynomials. For this last result are presented two proofs, one is due to Obrechko and another is due to Schoenberg. Finally, we present an application of the rule to the classical orthogonal polynomials of Jacobi and Laguerre